The Indonesian Version of the Chapron’s Screening Method for Endometriosis Diagnosis based on Questionnaire as a Tool for Better Endometriosis Screening in Indonesia - Hendrana, Aisyah Riseta Aini; Tjahyadi, Dian; Bayuaji, Hartanto; Rachmawati, Anita; Prasetyo, Nogi Eko; Djuwatono, Tono (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: This study aims to translate, develop, and assess the validity and reliability of the Indonesian version of Professor Chapron’s screening method for endometriosis diagnosis based on the questionnaire as a tool for better endometriosis screening in Indonesia.Methods: Development of the questionnaire using 5 steps: translation, synthesis, back translation, expert committee review, and pretesting by involving language expert and subject expert. The analysis includes the validity and reliability of the questionnaire.Results: A sample of 30 subjects was enrolled. The questionnaire was consist of 3 sections, including characteristic patient questions, yes or no questions (8 questions), and pain scale questions (5 questions). Of the 8 yes or no questions, 7 were valid (r >0.300), and one question was not valid (r<0.300). The yes or no questions were reliable (Cronbach’s alpha 0.6968). All of the 6 pain scale questions were valid (r>0.300) and reliable (Cronbach’s alpha 0.790).Conclusion: This study represent the Professor Chapron’s questionnaire for endometriosis screening into another language (Bahasa) than the original. It showed that the questionnaire was reliable, and one question was not valid (removed from the questionnaire). The questionnaire can be used in Indonesia for screening method in Indonesia.Versi Indonesia dari Kuesioner Chapron untuk Metode Skrining dalam Diagnosis Endometriosis sebagai Alat Skrining Endometriosis di IndonesiaAbstrak Tujuan: Penelitian ini bertujuan untuk menerjemahkan, mengembangkan, dan menilai validitas dan reliabilitas versi bahasa Indonesia dari metode Skrining Professor Chapron berdasarkan kuesioner, sebagai alat untuk skrining endometriosis yang lebih baik di Indonesia.Metode: Pengembangan kuesioner menggunakan 5 langkah: penerjemahan, sintesis, penerjemahan balik, telaah komite ahli, dan pra-uji dengan melibatkan ahli bahasa dan ahli subjek. Analisis yang dilakukan yaitu uji validitas dan reliabilitas kuesioner.Hasil: Sampel penelitian sebanyak 30 orang. Kuesioner terdiri atas 3 bagian, yaitu pertanyaan karakteristik pasien, pertanyaan ya atau tidak (8 pertanyaan), dan pertanyaan skala nyeri (5 pertanyaan). Sebanyak 7 pertanyaan ya atau tidak, hasilnya valid (r>0,300) dan 1 pertanyaan tidak valid (r<0,300). Pertanyaan ya atau tidak hasilnya reliabel (Cronbach’s alpha 0,6968). Semua pertanyaan skala nyeri hasilnya valid (r>0,300) dan reliabel (Cronbach’s alpha 0,7900).Kesimpulan: Penelitian ini mengembangkan serta menilai validitas dan reliabilitas kuesioner Professor Chapron untuk skrining endometriosis dalam versi bahasa Indonesia. Kuesioner ini reliabel dengan 1 pertanyaan tidak valid (dihilangkan dari kuesioner). Kuesioner ini dapat digunakan di Indonesia untuk metode skrining endometriosis di Indonesia.